Multi-Omics Characterization of a Glycerolipid Metabolism-Related Gene Enrichment Score in Colon Cancer - Wang, Zhiyu; Zhang, Zhuoqi; Zhang, Ke; Zhou, Qiaoxia; Chen, Sidong; Zheng, Hao; Wang, Guoqiang; Cai, Shangli; Wang, Fujing; Li, Shenglong (Frontiers in Oncology, 2022)
Background: Glycerolipid metabolism are involved in the genesis and progression of colon cancer. The current study aims at exploring the prognostic value and potential molecular mechanism of glycerolipid metabolism-related genes in colon cancer from the perspective of multi-omics. Methods: Clinical information and mRNA expression data of patients with colon cancer were obtained from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Single sample gene set enrichment analysis (ssGSEA) was applied to calculate the glycerolipid metabolism related-genes enrichment score (GLMS). Univariable and multivariable Cox regression analyses were used to study the prognostic value of GLMS in TCGA-COAD and GSE39582 cohorts. Molecular mechanism of the prognostic factor was investigated via immune cell infiltration estimation and correlation analysis of cancer hallmark pathways. Single cell transcriptomic dataset GSE146771 was used to identify the cell populations which glycerolipid metabolism targeted on. Results: The GLMS was found to be associated with tumor location and consensus molecular types (CMSs) of colon cancer in TCGA-COAD cohort (P<0.05). Patients in low-GLMS group exhibited poorer overall survival (OS) in TCGA cohort (P=0.03; HR, 0.63; 95% CI, 0.42-0.94), which was further validated in the GSE39582 dataset (P<0.001; HR, 0.57; 95% CI, 0.43-0.76). The association between the GLMS and OS remained significant in the multivariable analysis (TCGA cohort: P=0.04; HR, 0.64; 95% CI, 0.42-0.98; GSE39582 cohort: P<0.001; HR, 0.60; 95% CI, 0.45-0.80). The GLMS was positively correlated with cancer hallmark pathways including bile acid metabolism, xenobiotic metabolism, and peroxisome, and negatively correlated with pathways such as interferon gamma response, allograft rejection, apoptosis, and inflammatory response (P<0.05). Increased immune infiltration and upregulated expression of immune checkpoints was observed in patients with lower GLMS (P<0.05). Single cell datasets verified the different distribution of GLMS in cell subsets, with significant enrichment of GLMS in malignant cells and Tprolif cells. Conclusion: We demonstrated that GLMS was a potential independent prognostic factor for colon cancer. The GLMS was also correlated with several cancer hallmark pathways, as well as immune microenvironment.